PENGARUH MOTIVASI DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA PEGAWAI PADA DINAS PEHUBUNGAN KOTA SORONG - Sofia, Susetyowati; Rahayu, Agilistya; Maimuna, Maimuna (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to find out: (1) determine the influence of motivation on employee performance at the Sorong City Transportation Office, (2) determine the influence of the non-physical work environment on employee performance at the Sorong City Transportation Office, (3) find out the influence of motivation and non-physical work environment on employee performance at the Sorong City Transportation Office. This study used a correlation method using a quantitative approach. The population of this study is employees who work at the Sorong City Transportation Office which amounts to 77 people. The sample collection technique of this study used a saturated sample with a sample of 77 people. Data collection techniques by distributing questionnaires. The results of this study show that (1) motivation has a positive effect on employee performance at the Sorong City Transportation Office. This is evidenced by a significant value of 0.035 where the result is smaller than 0.05; (2) the non-physical work environment positively affects the performance of employees at the Sorong City Transportation Office. This is evidenced by a significant value of 0.002 where the result is smaller than 0.05; (3) motivation and non-physical work environment simultaneously affect the performance of employees at the Sorong City Transportation Office. This is evidenced by a significant value of 0.007 where the result is smaller than 0.05